Gestão de empreendimentos econômicos solidários: a experiência das incubadoras tecnológicas de economia solidária - Oliveira, Thaís Cristina Souza de (2018)
This research is based on a critical reflection on the studies of the Administration and seeks contributions to the management of solidarity enterprises, specifically by the practice of Technological Incubators of solidarity economy (ITES) that provide assessorship the enterprises of collectors of recyclable materials. It was considered the complexity and specificity of the management of these enterprises and the assumption that the technical assessorship services provided to these experiences are based, in most cases, on traditional business management and do not incorporate self-management mechanisms. Therefore, in order to search for new knowledge that could contribute to the management of self-managed enterprises, use the analysis of the experience of three incubators that operate with enterprises of collectors of recyclable materials for at least 10 years and, among the methodologies, tools and processes built with the incubated groups, sought to extract elements that help to think and build a management that is in keeping with the principles, specificities and needs of the solidary enterprises. The results indicated that the ITES analyzed based their activity on an education for self-management, seeking the construction of habits, values and conditions that favor the development of a democratic organization. It also presented as a challenge to the assessorship the conciliation between the various rationalities that permeate the organization and the elaboration of efficient technical solutions.